2017
DOI: 10.1002/ar.23583
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Suppresses Alkali Burn‐Induced Corneal Angiogenesis Along with a Downregulation of VEGFA and VEGFC Expression

Abstract: Triptolide (TPL) is an active compound extracted from a Chinese herbal medicine tripterygium wilfordii Hook. f. (Celastraceae), which has been used as an anti-inflammatory drug for years. It also inhibits the growth and proliferation of different types of cancer cells. The inhibitory effect of TPL on angiogenesis after chemical-induced corneal inflammation was studied in vivo. The effects of TPL on the proliferation, apoptosis, migration, and tube formation of rat aortic endothelial cells (RAECs) were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…Our results showed that the expression of PCNA in blood increased, but in skin decreased. Different from our results, another study reported increased expression of VEGF in the alkali burn-induced corneal angiogenesis mouse model ( 33 ). The decrease of VEGFA expression would induce the inhibition of angiogenesis ( 34 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that the expression of PCNA in blood increased, but in skin decreased. Different from our results, another study reported increased expression of VEGF in the alkali burn-induced corneal angiogenesis mouse model ( 33 ). The decrease of VEGFA expression would induce the inhibition of angiogenesis ( 34 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Membranes were blocked with a buffer containing Tris (10 mM, pH 7.4), NaCl (150 mM), Tween 20 (0.1%), and BSA (5%) and then incubated with the primary antibodies at a dilution of 1:1,000 at 4°C overnight. Subsequently, membranes were washed in TBST for 15 min twice and incubated with appropriate secondary antibodies for 2 h at room temperature (Wang et al, ). Bands and signals were collected by G: BOX Chemi XT4 (Syngene, UK).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate its effect on angiogenesis, it was tested in vitro and in vivo. Triptolide inhibited rat aortic endothelial cell migration and tube formation and significantly suppressed CoNV and VEGF expression in a murine alkali burn model [126]. While these results indicate that triptolide may have clinical indications for the treatment of CoNV, further studies are needed to assess its exact mechanism of action, optimal dose, and potential toxic side effects with long term use.…”
Section: Non-flavonoid Phytochemicalsmentioning
confidence: 94%